PENGENALAN BAHASA TULIS BERBASIS PEMEROLEHAN UNTUK ANAK KB DAN TK - Musfiroh, Tadkiroatun (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2008)
There are three main aspects of problems concerning the introduction ofthe written language (the language used in reading and writing activities) in playgroups and kindergartens: the method, the learning approach, and the media andsources used for the activities related to it. Inappropriateness in choosing the threeaspects will result in undesired development of the children on the whole,including their interest in reading and writing activities. Therefore, there needs tobe developed a model for introducing written language for children whichaccommodates the three aspects. A research study has been conducted with theobjective of developing and finalizing such a model and guidelines for itsapplication by means of (1) validation testing by experts and users, (2) limited fieldtesting, and (3) extended field testing.The research subjects were 107 teachers and 178 chidren in play groupsand kindergartens in the Yogyakarta Province. The data were obtained by means ofvarious methods: observation, questionnaire, interview, and documentation. Theinterview data were orthographically transcribed and then combined with fieldnotedata and data of the children's written expressions were documented by usinga scanner. The analysis was both qualitatively and quantitatively descriptive.Validity was confirmed by means of intra-rater and inter-rater techniques.The research results indicate that, after validation testing by experts andusers as well as limited and extended field testing, the model has shown an abilityto improve learning conditions, increase children's acquisition of the writtenlanguage for the related productive and receptive language activities, improvetheir symbol sensitivity, and strengthen the foundations of their reading andwriting activities. The application of the model has also improved the teachers'competence.Keywords: introducing written language, acquisition-based written language,children in play groups and kindergartens